(3GdGMJjGd ai GdbGfhf GdLfGFi (B: s (3OQGSI ebGQfI (B/ s - (3eMeO MSjf Ydi eMehO s; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JHOh CgejI gPg GdOQGSI hGVMI ShGA ef GdfGMjI GdfXQjI Ch GdfGMjI GdYedjI(B: (3Ch geG eYG fXQG ddGQJHGW GdcHjQ Hjf GdCeQjf; aef GdfGMjI GdfXQjI(B: (3JHOh gPg GdCgejI ERGdI GdZehV GdPi bO jcJfa HjGf CQcGf gPg GdLQjeI(B: (3h HjGf GdahGQb Hjfg h Hjf ZjQgG ef GdLQGFe GdJi bO JNJdW HgG eKd GdSQbI h NjGfI GdCeGfI h GSJZdGd MGLI GdbGUQ Ch Pi Gdghi(B: (3h gh CeQ HGdZ GdCgejI dGNJdGa GdYbGH GdebQQ dcd LQjeI ef gPg GdLQGFe(B: (3h dchf GdTQhY eYGbHG Ydjg HUOO HYVgG Ohf GdHYV GdBNQ(B. (3agh (B- (3Ef JhGaQJ CQcGfg (B- (3eYGbH Ydjg ai GdSQbI h GdfUH Ch GdGMJjGd(B: (3h djS eYGbH Ydjg ai GdLfM GdCNQi GdJi bO JNJdW HGdfUH(B. (3h ef GdfGMjI GdYedjI(B: (3aEf SHQ CZhGQ gPg GdLQjeI jSGYO CYVGA GdfjGHI GdYGeI Ydi EYWGA GdJcjja GdUMjM ddhGbYI GdeKGQI CeGege(B: (3Hd h JHOh gPg GdCgejI cPdc HGdfSHI ddbGVi(B: (3YfO EYWGFg GdJcjja GdfgGFi h GdUMjM ddhGbYIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B297-306s
Keywords: (3GdJWhQ GdJGQjNj dLQjeI GdfUH hGdGMJjGds; (3eGgjI LQjeI GdfUH ChGdGMJjGds; (3GdeUdMI GdeMejI aj LQjeI GdfUH Ch GdGMJjGds; (3WHjYI LQjeI GdfUH Ch GdGMJjGds; (3GdQcf GdeGOi dLQjeI GdfUH s; (3GdfTGW GddGRe dbjGe LQjeI GdfUH s; (3GdfJjLI GdGLQGejI aj LQjeI GdfUHs; (3YdGbI GdSHHjI aj LQjeI GdfUH s; (3GdQcf GdeYfhj dLQjeI GdfUHs; (3QSGFd LGeYI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs